GAMBARAN PERENCANAAN OBAT DENGAN METODE ANALISIS ABC DI APOTEK ALETHEIA SEMARANG PERIODE JANUARI - DESEMBER 2024 - Solichah, Ayu Ina; Anggun Ayuningtias Putri; Eleonora Maryeta Toyo (Journal Pharma Saintika, 2025)
Medication planning is a crucial component of the medication management process in pharmacies. Poor drug planning can lead to budget inefficiencies in procurement, resulting in ineffective spending and unavailability of medicines in the right quantity and at the right price. This study aims to analyze the ABC classification of medications at Aletheia Pharmacy, Semarang. A quantitative descriptive method was used by collecting and analyzing all sales data to describe how drug planning and procurement are conducted, using retrospective data and available sales documents from January to December 2024. The ABC method begins with collecting pharmacy sales data, followed by calculating the percentage contribution of each item to the total sales value. The medications are then grouped into three categories: Category A for high-value items, Category B for medium-value items, and Category C for low-value items. Planning is then carried out by prioritizing Category A medications, while Categories B and C are managed with simpler approaches. From the analysis, a total of 1,260 medication items were identified. Category A consisted of 369 items (29.3%) with an investment value of Rp. 271,123,000 (70.96%). Category B included 425 items (33.7%) with an investment value of Rp. 76,369,000 (19.99%). Category C comprised 466 items (37%) with an investment value of Rp. 34,422,100 (9.01%).